Android Mobile Devices Context Based Access Control Systems (International Journal of Innovative Research in Engineering & Management, 2023)
The Mobile applications designed for An droid frequently have access to private information and re sources stored on the user's device. The improper use of this  data by malicious programs has the potential to result in  breaches of privacy as well as the disclosure of sensitive  data. An example of this would be a malicious application  capturing a confidential business chat in the background  without the user's knowledge. The issue is caused by the fact  that Android users do not have control over the capabilities  of programs once those applications have been granted the  desired access during installation. This is what causes the  problem. It is necessary for us to have a context-based ac cess control mechanism so that privileges can be dynamical ly provided or revoked to applications based on the specific  context of the user. This is because there are numerous situa tions in which the possibility that an application will be al lowed a privilege is contingent on the specific context of the  user. In this article, we suggest an access control system  along these lines. Our implementation of context distin guishes between subareas that are geographically adjacent to  one another within the same location. We have made certain  changes to the Android operating system in order to enable  context-based access control limitations, which can then be  set and implemented. We have carried out a number of tests  in order to evaluate both the efficacy of our access control  mechanism and the precision of context recognition.
Keywords: Android Mobile; Smart Phone; Security And Privacy; Context Based Access Control